High-speed line-scan confocal Raman microscope with enhanced diffraction efficiency - Xing, Jingchao; Kang, Sung Hoon; Choi, Young Man; Lee, Seungwoo; Yoo, Hongki (Measurement Science and Technology, 2020)
Confocal Raman microscopy is commonly employed across different research fields because it allows for label-free sample investigation at high spatial resolution. However, the slow data acquisition speed of Raman microscopy limits its application for imaging large area samples. We developed a line-scan confocal Raman microscope to achieve parallel detection for high-speed data acquisition and proposed a dual mirror scan method to enhance the diffraction efficiency of the spectrometer. We used a Powell lens for the line illumination and demonstrated that it can provide a more uniform intensity distribution than a cylindrical lens. The spectrometer consists of a volume phase holographic grating and two scanning mirrors. Using the proposed dual mirror scan method can provide a high-resolution Raman spectrum at high efficiency over a wide spectral range. The system has a maximum spectral rate of 25 600 spectra s-1 and a theoretical spectral resolution of 1.2 cm-1. With the parallel detection by the line illumination and the enhanced diffraction efficiency, we expect the proposed system can be used in a variety of applications that require a high spectral rate, such as wide-field Raman imaging.
Keywords: Confocal Raman microscopes; Confocal Raman microscopy; Data acquisition speed; High spatial resolution; High speed data acquisition; Phase grating; Raman imaging; Volume phase holographic gratings; Confocal Raman microscopy; high-speed Raman imaging; spectrometer; volume phase grating